LE RAPORT DE STAGE JE SUIS JOURNALISTE STAGIAIRE Ã ANTARA (LEMBAGA KANTOR BERITA NASIONAL) - , PUTERI SYOFYANITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This report discusses the results of the report as a reporter internship in the Public Enterprise National News Agency Antara or Perum LKBN Antara. LKBN Antara national press company located in central Jakarta. This report contains background, problem formulation and implementation purposes internship in LKBN. The company profile includes history, location, and other news directorate also loaded based on source data acquired during the internship. The report also includes activities for implementing the practice of the author of an apprenticeship as a journalist in the editorial general news reinforced by the attachment of images and attachments story ever published on the website and the various portals Antara onlien. As a complement, the report is also accompanied by conclusions and suggestions for Perum LKBN Antara.